Analysis on Policy Implementation of Community Health Center as Report Obligation Recipient Institution for Narcotic Addicts in Jakarta Province in 2014 - Wahyuni, Sri Puji; Bachtiar, Adang (Journal of Indonesian Health Policy and Administration, 2015)
This paper analyzed the Policy Implementation of Community Health Center (CHC) as Report Obligation Recipient Institution for Narcotic Addicts in Jakarta Province in 2014. The design of the study employed a mixed methods approach of Sequential Explanatory. The implementation analysis employed the model developed by Donald Van Meter and Carl Van Horn. Within the model, policy implementation was associated with performance. The relationship was influenced by six variables: standards and targets, resources, communication among implementing agencies, implementing agency characteristics, attitudes of the implementers, as well as social, economic, and political factors. We found that variations of those six variables influenced policy performance linearly.